Epitope mapping of anti‐myelin oligodendrocyte glycoprotein (MOG) antibodies in a mouse model of multiple sclerosis: microwave‐assisted synthesis of the peptide antigens and ELISA screening. (10th December 2015) - Pacini, Giulia; Ieronymaki, Matthaia; Nuti, Francesca; Sabatino, Giuseppina; Larregola, Maud; Aharoni, Rina; Papini, Anna Maria; Rovero, Paolo
Abstract : The role of pathologic auto‐antibodies against myelin oligodendrocyte glycoprotein (MOG) in multiple sclerosis is a highly controversial matter. As the use of animal models may enable to unravel the molecular mechanisms of the human disorder, numerous studies on multiple sclerosis are carried out using experimental autoimmune encephalomyelitis (EAE). In particular, the most extensively used EAE model is obtained by immunizing C57BL/6 mice with the immunodominant peptide MOG(35–55). In this scenario, we analyzed the anti‐MOG antibody response in this model using the recombinant refolded extracellular domain of the protein, MOG(1–117). To assess the presence of a B‐cell intramolecular epitope spreading mechanism, we tested also five synthetic peptides mapping the 1–117 sequence of MOG, including MOG(35–55). For this purpose, we cloned, expressed in Escherichia coli and on‐column refolded MOG(1–117), and we applied an optimized microwave‐assisted solid‐phase synthetic strategy to obtain the designed peptide sequences. Subsequently, we set up a solid‐phase immunoenzymatic assay testing both naïve and EAE mice sera and using MOG protein and peptides as antigenic probes. The results obtained disclose an intense IgG antibody response against both the recombinant protein and the immunizing peptide, while no response was observed against the other synthetic fragments, thus excluding the presence of an intramolecular epitope spreading mechanism. Furthermore, as the properly refolded recombinant probe is able to bind antibodies with greater efficiency compared with MOG(35–55), we hypothesize the presence of both linear and conformational epitopes on MOG(35–55) sequence. Copyright © 2015 European Peptide Society and John Wiley & Sons, Ltd. Abstract : The most extensively studied multiple sclerosis animal model is experimental autoimmune encephalomyelitis, obtained by immunizing mice with MOG(35–55) peptide. To evaluate the anti‐MOG antibody response in this model, we tested the recombinant refolded MOG(1–117) as antigenic probe. We also assessed the presence of intramolecular epitope spreading testing five synthetic peptides mapping the 1–117 sequence. Our results suggest the presence of both linear and conformational epitopes on MOG(35–55) sequence.